Effects of Liquid Epoxidized Natural Rubber (LENR) on the Mechanical Properties of Epoxy Matrix Composites - Mohammad, Noorshashillawati Azura; Haji Ahmad, Sahrim; Mohammad, Nurul Emi Nor Ain; Mohd Hassan, Nurul Husna (International Journal of Integrated Engineering, 2018)
The aim of this study was to investigate the mechanical properties of brittle epoxy resin when modified by liquid epoxidized natural rubber for toughening purposes. In this study, liquid epoxidized natural rubber (LENR) was introduced to the epoxy with five different loadings of 1%, 3%, 5%, 7% and 9% by weight. The mechanical strength (flexural strength, flexural modulus, tensile strength, tensile modulus and impact strength) of the rubber toughened epoxy composites were investigated. The results showed that the addition of liquid epoxidized natural rubber (LENR) had improved the flexural modulus, flexural strength and impact strength by 47%, 40%, and 22% respectively at 3% loading.